Closure operators associated with relations - ˇSlapal, Josef (Topology Proceedings, 2022)
We study closure operators that are associated with α-ary relations where α>1 is an ordinal. In particular, we show that the connectedness with respect to the closure operators is a certain kind of path-wise connectedness. We demonstrate a possible application of our results in digital topology.